(untitled) (Itinera, 2023)
Marcel Proust’s novels certify kitsch by the presence of architecture, theater and fashion. The writer produced his works using textual accumulation and hybridization. These two processes call for other arts in romantic production. From this point of view, the baroque, gothic and modern architectures are represented in the texts through buildings tested by rhetorical descriptions. Images of theater and opera scenes accentuate the flow of kitsch. Ostentatious mode creations are also notified in the intrigues. Marcel Proust is inspired by performing arts to develop an aesthetic of plurality in his novels.